Agricultural expansion as risk to endangered wildlife: Pesticide exposure in wild chimpanzees and baboons displaying facial dysplasia - Krief, Sabrina; Berny, Philippe; Gumisiriza, Francis; Gross, Régine; Demeneix, Barbara; Baptiste Fini, Jean; Chapman, Colin A.; Chapman, Lauren J.; Seguya, Andrew; Wasswa, John (Science of the Total Environment, 2017)
Prenatal exposure to environmental endocrine disruptors can affect development and induce irreversible abnormalities in both humans and wildlife. The northern part of Kibale National Park, a mid-altitude rainforest in western Uganda, is largely surrounded by industrial tea plantations and wildlife using this area (Sebitoli) must cope with proximity to human populations and their activities. The chimpanzees and baboons in this area raid crops (primarily maize) in neighboring gardens. Sixteen young individuals of the 66 chimpanzeesmonitored (25%) exhibit abnormalities including reduced nostrils, cleft lip, limb deformities, reproductive problems and hypopigmentation. Each pathology could have a congenital component, potentially exacerbated by environmental factors. In addition, at least six of 35 photographed baboons from a Sebitoli troop (17%) have similar severe nasal deformities. Our inquiries in villages and tea factories near Sebitoli revealed use of eight pesticides (glyphosate, cypermethrin, profenofos, mancozeb, metalaxyl, dimethoate, chlorpyrifos and 2,4-D amine). Chemical analysis of samples collected from 2014 to 2016 showed that mean levels of pesticides in fresh maize stems and seeds, soils, and river sediments in the vicinity of the chimpanzee territory exceed recommended limits. Notably, excess levels were found for total DDT and its metabolite pp′-DDE and for chlorpyrifos in fresh maize seeds and in fish from Sebitoli. Imidacloprid was detected in coated maize seeds planted at the edge the forest and in fish samples from the Sebitoli area, while no pesticides were detected in fish from central park areas. Since some of these pesticides are thyroid hormone disruptors, we postulate that excessive pesticide use in the Sebitoli area may contribute to facial dysplasia in chimpanzees and baboons through this endocrine pathway. Chimpanzees are considered as endangered by IUCN and besides their intrinsic value and status as closely related to humans, they have major economic value in Uganda via ecotourism. Identifying and limiting potential threats to their survival such be a conservation priority.
Keywords: Endocrine disruptors; Pesticides; Non-human primates; Apes; Monkeys; Uganda